Publicization of Violence and Crime: Reality Shows and Their Social Impacts - (:unkn) unknown (MARMARA UNIV, FAC COMMUNICATION, 2019)
The assumption that violence and crime contents increase ratings leads to presentation of such themes to viewers through news bulletins, crime series and reality shows. Previous researches show that programs that include violence and crime influence the attitudes of viewers depending on the content, ratings, type of programs and language of discourse. As far as non-fictional reality show viewership is concerned, television can unearth an individual's tendency towards violence but does not play a role in consolidating it. On the other hand, the viewer who watches such programs might develop a fear that s/he can become a victim of violence and crime. This paper will analyse the relationships between tendency towards violence, violent and criminal behaviour and viewing non-fictional reality shows. In order to analyse these relationships, the origins of violent behaviour are explained and programs are compared according to their types, methods and impacts. Finally, the paper tries to identify social impacts of reality shows in the context of risk and fear, as programs that discuss crimes and at times co-operates with security forces. This paper shows that the factuality of fear of victimhood should be analysed by taking qualitative probability of victimhood rather than statistical data regarding violent and criminal incidents.
Keywords: Media; Television; Reality Shows; Crime; Violence; PRIME-TIME; MEDIA; FEAR